Memantik Ketrampilan Sosial Siswa Melalui Model Pembelajaran Two Stay-Two Stray (TS-TS) - Lisdiana, Anita (Tarbawiyah Jurnal Ilmiah Pendidikan, 2019)
The purpose of this study was to determine the use of the TS-TS learning model for students' social skills in MTs Al-Hikmah Bandar Lampung on Integrated Social Sciences subjects. This research is a class action research. The populations in this study were students of MTs Al-Hikmah Bandar Lampung and the sample in this study were students of class VII A MTs Al-Hikmah Bandar Lampung. Data collection in this study was carried out by observation, interview, and documentation. The results showed that there was an increase in students' social skills at MTs Al-Hikmah Bandar Lampung using the TS-TS learning model. In the cycle 1 phase there are no indicators of student social skills reaching 70%. In the second cycle phase, the social skills indicator of students reached 70%, namely the indicator of the ability to share information reaching 73%, the indicator of the ability to take seriously / follow instructions reaching 75% and the indicator of the ability to work together to reach 77%. In the third cycle stage, all indicators of students' social skills have reached 70% or more. Indicator of the ability to share information reached 82%, indicator of the ability to respect reached 80%, indicator of the ability to be serious / follow the instructions reached 86%, indicator of the ability to work together reached 84%, indicator of the ability to express opinions reached 82% and indicator of the ability to accept opinions reached 84%. Improvement of students 'social skills in each cycle strengthens the evidence that the use of TS-TS learning models provides alternative learning that can improve students' social skills.